A combined adjuvant and ferritin nanocage based mucosal vaccine against Streptococcus pneumoniae induces protective immune responses in a murine model - Tien Duc Nguyen; Hoang Duy Le; Giang Chau Dang; Hyun Seok Jung; Yoonjoo Choi; Koemchhoy Khim; Young Kim; Shee Eun Lee; Joon Haeng Rhee (Nature Communications)
Abstract Protein nanocages are multimeric structures that can be engineered to mimic the molecular conformation of microorganisms. Based on previous findings showing that a mucosal FlaB-tPspA fusion (flagellin fused with truncated PspA antigen of Streptococcus pneumoniae) vaccine-induced protective immune response against S. pneumoniae, we develop a ferritin nanocage vaccine displaying multivalent presentation of both antigen and adjuvant on a nanocarrier using the SpyTag/SpyCatcher strategy. The 1:1 antigen/adjuvant nanocage is further used as a mucosal vaccine, which can translocate to draining lymph nodes with higher efficiency than fusion vaccine. Moreover, intranasal immunization with the nanocage vaccine significantly enhances mucosal immune responses with more efficient B-cell memory generation and antibody maturation, as well as more balanced (Th1/Th2) immune responses with increased IFN-γ and IL-17 production, comparing with fusion vaccine. Mice immunized with the nanocage vaccine exhibited enhanced protection against lethal infection compare to the FlaB-tPspA fusion group. Our study thus demonstrates the effectiveness of an all-in-one nanocage mucosal vaccine platform, which guarantees enhanced protection with balanced immune responses.